2017
DOI: 10.1155/2017/2156478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tissue Harvesting Sites on the Cellular Behaviors of Adipose-Derived Stem Cells: Implication for Bone Tissue Engineering

Abstract: The advantages of adipose-derived stem cells (AdSCs) over bone marrow stem cells (BMSCs), such as being available as a medical waste and less discomfort during harvest, have made them a good alternative instead of BMSCs in tissue engineering. AdSCs from buccal fat pad (BFP), as an easily harvestable and accessible source, have gained interest to be used for bone regeneration in the maxillofacial region. Due to scarcity of data regarding comparative analysis of isolated AdSCs from different parts of the body, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
0
14
0
5
Order By: Relevance
“…Mesenchymal stem cells are widely used for the treatment of damaged tissues, following trauma or other pathological culprits (Caplan, 2007). Even though bone marrow represents the mostly used source of MSCs in the clinical field, adipose tissue may serve as a valid alternative (Rezai Rad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells are widely used for the treatment of damaged tissues, following trauma or other pathological culprits (Caplan, 2007). Even though bone marrow represents the mostly used source of MSCs in the clinical field, adipose tissue may serve as a valid alternative (Rezai Rad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In another investigation, De Angelis et al reviewed the surgical results of 20 patients, who experienced the application of Dermal Regeneration Template (DRT) for scalp reconstruction for minor defects. During 3 weeks, De Angelis et al observed the complete healing of the wound bed by secondary intention with suitable cosmetic outcomes and firm scars [54]. Currently, no consistent technique for the extraction of adipose tissue exists.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, among them, the expression of osteogenic markers were higher in BFP-AD-MSCs, suggesting that BFP-AD-MSCs may represent an interesting source of MSCs for bone defect treatment tissue engineering [187].…”
Section: Cells and Tissue-sourcesmentioning
confidence: 99%